Composição química e avaliação da atividade anticandida do óleo essencial de Lippia origanoides Kunth (Verbenaceae) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
Fungal infections make up a growing and significant public health problem. Of the infections caused by fungi, Candidiasis stands out for its endogenous opportunistic behavior, since it occurs in host tissues that present compromise of its specific or non-specific defense systems The constant emergence of strains resistant to the main conventional antifungals has led researchers to race in search of new effective and safe alternatives. Therefore, important studies related to the antifungal activity of products of plant origin have shown promising results in the discovery of active principles that can be used in the treatment of infections caused by microorganisms, among them fungi. The objective of the research was to determine the chemical composition and to evaluate the anti-candida potential of the essential oil of Lippia origanoides Kunth. The chemical composition of the essential oil of L. origanoides was determined by means of the GC-EM (Gas Chromatography - Mass Spectrometry) technique, presenting carvacrol (47.2%) and thymol (12.8%) as the main volatile compounds. To evaluate the anti-Candida potential of L. origanoides, two methodologies were used: disc diffusion in agar and microdilution in broth. The essential oil of L. origanoides was tested against 3 yeast strains: Candida albicans, C. tropicalis and C. parapsilosis, showing efficacy in the inhibition of growth of the three strains evaluated, with inhibition halos ranging from 44.1 ± 0, 3, 30.6 ± 0.2 and 24.0 ± 0.1 mm in diameter, respectively. The MICs (Minimal Inhibitory Concentration) were determined in 0.62 μl / mL against C. albicans, 0.30 μl / mL against C. tropicalis and 0.18 μl / mL against C. parapsilosis. Fluconazole, revealed MIC values of 0.125 for C. albicans and C. tropicalis, and 0.010 for C. parapsilosis. Thus, it is observed that the essential oil of L. origanoides showed activity against three strains of Candida, and that its ability to decrease or eliminate the microorganism depends on the concentration tested.
Keywords: Fungos; óleos essenciais; Candida; CNPQ:: CIÊNCIAS BIOLÓGICAS